Mathematical rationale for the recovery of defects of hard tissues of teeth pulpless ceramic inlays - D. A. Bronstein; A. Y. Lerner; R. U. Bersanov; A. V. Zharov; M. A. Amirkhanian (Кубанский научный медицинский вестник, 2015)
On the three-dimensional mathematical model of the upper molars mapped stress-strain state on the border of dental hard tissues with ceramic inlays or composite restorations. Set permissibility of the use of composite restorations in molars with intact pulp, but the necessity of recovery from the standpoint of biomechanics defect depulpirovannogo tooth ceramic inlays.